THU0165 High rate of cardiovascular events in lupus patients at 5 year follow up and association of classical and lupus related risk factors. (23rd January 2014) - Skeoch, S.; Haque, S.; Parker, B.; Ahmad, Y.; Teh, L.S.; Bruce, I.
Abstract : Background: Patients with systemic lupus erythematosus (SLE) are at increased risk of cardiovascular disease. This is thought to be due to both increased incidence of classical risk factors and SLE related risk factors (1). Objectives: To investigate the incidence of cardiovascular events (CVEs) in SLE patients and the association with classical risk factors and SLE disease features. Methods: Cardiovascular risk factors and SLE disease characteristics were evaluated in 200 female SLE patients. A subgroup was followed up at 5 years and CVEs (defined as myocardial infarction, angina, coronary angioplasty, coronary artery bypass surgery, stroke, transient ischaemic attack or peripheral vascular disease) were recorded. 5 year risk of CVE at baseline was calculated using the Framingham risk equation (2) and association of baseline measurements with subsequent CVEs were tested using non-parametric tests and linear regression models, adjusting for age. Results: 124 patients were followed up at a median (IQR) of 5.8 (5.2, 6.3) years. At follow up, median (IQR) age was 55.6 (49.8, 62.4) years and disease duration was 16.3 (9.8, 23.5) years. At baseline, median (IQR) SLEDAI disease activity score was 1 (0, 4) and SLICC damage index was 0 (0, 1). 12 patients had suffered prior CVEs. The only significant difference at baseline between those who were and were not followed up was systolic blood pressure (132.2mmHg vs 124.7mmHg, p=0.015). At follow up, 12 patients had suffered a CVE giving a 10.2% 5 year CVE rate. Baseline predictors of CVEs (OR [CI 95%]) were hypertension (6.19[1.50, 25.47]), prior CVE (4.89[1.15, 20.65]), triglyceride levels (2.92[1.30, 6.46]), cyclophosphamide exposure (4.20[1.77, 35.0]) and SLICC damage index (1.77[1.15, 2.62]). Venous thromboembolism (2.51[0.95, 6.66]), azathioprine exposure (3.30[0.94, 11.58]), metabolic syndrome (3.26[0.95, 11.28]) and disease duration (1.04[0.97, 1.43]) showed at trend towards significance. 8 of the 12 patients had no prior history of CVEs, giving a 7% 5 year primary CVE rate, this compared to our estimated median (IQR) 5 year risk using the Framingham risk equation of 1 (1, 3)%. Estimated risk was not significantly associated with subsequent CVE (OR 1.09 [CI95%0.88, 1.35]) and point estimates for cyclophosphamide exposure and triglyceride levels remained similar to in the population free of CVEs at baseline (4.20 [1.77, 35.0] vs 4.96 [0.77, 31] and 2.92 [1.3, 6.65] vs 2.55 [0.95, 6.8] respectively). Conclusions: Our SLE cohort had a 7-fold increased risk of CVEs compared to what is predicted from the Framingham risk scores.The associations of cyclophosphamide exposure and SLICC damage index with future CVEs suggests disease severity may contribute to risk. We also noted that dyslipidaemia may contribute to CVE risk in SLE. Patients with more severe disease may be particularly at risk of future cardiovascular disease. References: Bruce IN. "Not only ... but also": factors that contribute to accelerated atherosclerosis and premature coronary heart disease in systemic lupus erythematosus. Rheumatology (Oxford) 2005 Dec;44(12):1492-502. Anderson KM, Wilson PW, Odell PM, Kannel WB. An updated coronary risk profile. A statement for health professionals. Circulation 1991 Jan;83(1):356-62. Disclosure of Interest: None Declared